Fasciculoventricular pathways—A rare and innocent variant: A Retrospective study focusing on clinical and electrophysiologic characteristics. Issue 3 (2nd January 2022) - Gormel, Suat; Yasar, Salim
Abstract: Background: Fasciculoventricular pathways (FVPs) are variants of pre‐excitation syndrome which were investigated insufficiently because of its rarity. Objective: This report aimed to represent one of the largest series of FVP, focusing on its clinical and electrophysiological properties. Methods: We analyzed retrospectively 26 consecutive patients who underwent electrophysiological study (EPS) for FVP between January 1998 and June 2020. Results: Among 1437 patients with accessory pathways, 26 had FVP (1.80%). All the 26 patients (100%) were males, with a mean age of 22.15 ± 3.50 years (range, 20–34 years). In the baseline electrocardiograms of the patients with FVP, pre‐excitation and transitional zone were seen in leads V2 –V4 . During EPS procedures, normal AH interval and shortened HV interval were detected. All the patients had AH prolongation after atrial pacing due to atrioventricular (AV) nodal delay without change in pre‐excitation degree. Five of the FVP patients (19.2%) had extra accessory pathways, all of which were ablated successfully while the FVPs were followed clinically. Conclusion: Fasciculoventricular pathways are uncommon variants of pre‐excitation syndrome; therefore, they should be diagnosed correctly and followed up noninvasively to avoid damages.